International consensus on quality standards for brain health-focused care in multiple sclerosis. (November 2019) - Hobart, Jeremy; Bowen, Amy; Pepper, George; Crofts, Harriet; Eberhard, Lucy; Berger, Thomas; Boyko, Alexey; Boz, Cavit; Butzkueven, Helmut; Celius, Elisabeth Gulowsen; Drulovic, Jelena; Flores, José; et al.
Background: Time matters in multiple sclerosis (MS). Irreversible neural damage and cell loss occur from disease onset. The MS community has endorsed a management strategy of prompt diagnosis, timely intervention and regular proactive monitoring of treatment effectiveness and disease activity to improve outcomes in people with MS. Objectives: We sought to develop internationally applicable quality standards for timely, brain health–focused MS care. Methods: A panel of MS specialist neurologists participated in an iterative, online, modified Delphi process to define 'core', 'achievable' and 'aspirational' time frames reflecting minimum, good and high care standards, respectively. A multidisciplinary Reviewing Group (MS nurses, people with MS, allied healthcare professionals) provided insights ensuring recommendations reflected perspectives from multiple stakeholders. Results: Twenty-one MS neurologists from 19 countries reached consensus on most core (25/27), achievable (25/27) and aspirational (22/27) time frames at the end of five rounds. Agreed standards cover six aspects of the care pathway: symptom onset, referral and diagnosis, treatment decisions, lifestyle, disease monitoring and managing new symptoms. Conclusion: These quality standards for core, achievable and aspirational care provide MS teams with a three-level framework for service evaluation, benchmarking and improvement. They have the potential to produce a profound change in the care of people with MS.